7th International Workshop on Graph Based Tools (GraBaTs 2012): Preface - Krause, Christian; Westfechtel, Bernhard (Electronic Communications of the EASST, 2012)
The 7th International Workshop on Graph Based Tools is the continuation of the GraBaTs series of workshops which provides a forum for researchers and practitioners interested in the development and application of graph-based tools. The purpose of this workshop is to survey the state of the art of graph-based tools, bring together developers of graph-based tools in different application fields and to encourage new tool development cooperations. GraBaTs 2012 is the 7th edition in a line of workshops which started 10 years ago at ICGT’02.